Perancangan Sistem Pemesanan Makanan Berbasis Web pada UMKM dengan Framework Laravel - Fadhliansyah, Ahmad; Wibowo, Edi; Panji, Krisna (LPPM STT Terpadu Nurul Fikri, 2025)
Mie Ayam & Bakso Mas Dava is a culinary MSME that still uses manual order recording, often leading to errors, long queues, and service delays. This study aims to design a webbased ordering application to improve operational efficiency, reduce recording errors, and simplify order and sales management. The development method used is Extreme Programming (XP), which includes planning, design, coding, testing, and evaluation phases. The application was developed using the Laravel framework, supported by Tailwind CSS, HTML, MySQL, and integrated with Midtrans as a payment gateway. Key features of the system include menu ordering, shopping cart, special order notes, order status tracking, and an admin dashboard for managing products and sales reports. Testing using the Black Box testing method shows that the system is 100% running as expected.. Evaluation involving 15 users showed that the application is easy to use and speeds up the ordering process. The business owner also confirmed that the system significantly reduces recording errors and improves service efficiency. Based on these results, the application is considered feasible for implementation and has the potential to be further developed to support the digital transformation of culinary MSMEs.